Influence of Innovation Strategies on the Performance of Insurance Firms in Kenya - Mugendi, Kyalo Stanley; Kihara, Allan (Journal of Business and Strategic Management, 2024)
Purpose: The purpose of this study was to establish how innovative methods affect the performance of Kenyan insurance companies. The precise goals encompass establishing the impacts of market innovation, product innovation, service innovation and pricing innovation on performance. Methodology: The study targeted all the 54 insurance firms registered by IRA. The sample size featured 162 respondents representing three respondent from each firm. Questionnaires were used to collect data from the respondents and the five-point Likert scale was used to construct the questions. Data analysis was done using correlation and regression analyses through SPSS. The results indicated that that overall market innovation had greater impact on financial performance. Advertisements and promotional strategies were associated with more positive impact and these may be the specific strategies that firms should focus on. Findings: The overall positive results were also experienced by price innovation as price undercutting and offering discounts exhibited greater positive influence. The overall impact of service innovation and product innovation was established to be negative. Nevertheless, when assessed specifically, improving existing products had positive influences. Similarly for service innovation, improving old services recorded positive impacts relative to providing complementary services. In light of these results, the study recommended that firms be strategic and specific when implementing innovation strategies. Unique Contributions to Theory, Policy and Practice: Also, the study recommended that firms support product innovation with market research, build an organizational culture that encourages, supports, and reward innovation, and encourage innovation mix to build greater success and foster holistic growth.